The Role of Islamic Religious Education in Forming Students' Religious Character - Jauhari, Mohamad Nasich (STAI MA'ARIF MAGETAN, INDONESIA, 2022)
Islamic religion education is education to prepare students to believe, understand, appreciate, and practice the religion of islam to form personal qualities so as to produce faith and religious spiritualachievements in students. This research includes library research using a descritive approach, the data obtained in the form of supporting literature.method of collecting data with dokumentation, while the documents used are in the form of relevant book. The data validity technique used is theoretical triangulation. Technique with content analysis is a method for making conclusions or research result by identifying specific characteristics objectively and systematically. The role of islamic religious education in making the character of students who are eeligious by habituation of exemplary and rules.